Hanns and Rudolf : the true story of the German Jew who tracked down and caught the Kommandant of Auschwitz - Harding, Thomas, 1968- (New York : Simon & Schuster, 2013)
May 1945. In the aftermath of the Second Word War, the first British War Crimes Investigation Team is assembled to hunt down the senior Nazi officials responsible for the greatest atrocities the world has ever seen. One of the lead investigators is Lieuten
Rudolf, Baden-Baden, Germany, 1901 -- Hanns, Berlin, Germany, 1917 -- Rudolf, Berlin, Germany, 1918 -- Hanns, Berlin, Germany, 1928 -- Rudolf, Berlin, Germany, 1928 -- Hanns, Berlin, Germany, 1933 -- Rudolf, Oswiecim, Upper Silesia, 1939 -- Hanns, London, England, 1939 -- Rudolf, Oswiecim, Upper Silesia, 1942 -- Hanns, Normandy, France, 1945 -- Rudolf, Berlin, Germany, 1943 -- Hanns, Brussels, Belgium, 1945 -- Rudolf, Berlin, Germany, 1945 -- Hanns, Belsen, Germany, 1945 -- Hanns and Rudolf, Gottrupel and Belsen, Germany, 1946 -- Hanns and Rudolf, Gottrupel, Germany, 1946 -- Hanns and Rudolf, Belsen and Nuremberg,Germany, 1946
Includes bibliographical references (pages 333-335) and index.
Keywords: Auschwitz (Concentration camp) -- Officials and employees -- Biography; 1900-1947.; Alexander, Hanns, -- 1917-2006.; Great Britain. -- Army -- Officers -- Biography; Jews -- Germany -- Biography; Jews -- Great Britain -- Biography; War criminals -- Germany -- Biography; Concentration camp commandants -- Poland -- Biography